GELFAND THEOREM FOR BANACH HYPERALGEBRAS - Parvinianzadeh, Rohollah; Taghavi, Ali (Italian Journal of Pure and Applied Mathematics, 2016)
In this paper, we prove that if A is a commutative Banach hyperalgebra then the maximal w-hyperideal space of A is in one-to-one correspondence with the set of (proper) maximal w-hyperideal in A. Also, we obtain some interesting results in direction.